Stereo-video landers can rapidly assess marine fish diversity and community assemblages - Kinsey E. Matthews; Ryan T. Fields; Kathleen P. Cieri; Jacklyn L. Mohay; Mary G. Gleason; Richard M. Starr (Frontiers in Marine Science, 2024)
Climate change and anthropogenic stressors affect the distribution, abundance, and diversity of fish communities across the world. To understand rapidly changing biotic communities, resource managers need a method to quickly and efficiently document temporal and spatial changes in community assemblages across various spatial scales. In this study, we describe the use of new video lander tools to survey fish communities in rocky marine habitats on the continental shelf and slope in California, USA. We evaluate how fish diversity metrics determined by video surveys vary among geographically distinct areas. Our results demonstrate that species diversity, evenness, and richness vary spatially across the coast. Furthermore, community assemblages differ at both broad and fine spatial scales because of differences among habitats. Length frequencies and densities of species in this study were similar to those reported in previous studies. As community assemblages and biodiversity metrics shift in response to changing stressors, it is increasingly important to develop tools and methodologies to detect and rapidly monitor these changes.

Balancing Model Complexity, Data Requirements, and Management Objectives in Developing Ecological Reference Points for Atlantic Menhaden - Katie Drew; Matthew Cieri; Amy M. Schueller; Andre Buchheister; David Chagaris; Geneviève Nesslage; Jason E. McNamee; James H. Uphoff (Frontiers in Marine Science, 2021)
Atlantic menhaden is an important forage fish and the target of the largest fishery along the US East Coast by volume. Since 1999, managers at the Atlantic States Marine Fisheries Commission, stakeholders, and scientists have been interested in developing ecological reference points (ERPs) that account for menhaden’s role as a forage species. To accomplish this, we developed a suite of modeling approaches that incorporated predation on menhaden and changes in productivity over time and allowed for evaluation of trade-offs between menhaden harvest and ecosystem management objectives. These approaches ranged in complexity, from models with minimal data requirements and few assumptions to approaches with extensive data needs and detailed assumptions. This included a surplus production model with a time-varying intrinsic growth rate, a Steele-Henderson surplus production model, a multispecies statistical catch-at-age model, an Ecopath with Ecosim (EwE) model with a limited predator and prey field, and a full EwE model. We evaluated how each model could address managers’ objectives and compared outputs across the approaches, highlighting their strengths, weaknesses, and management utility. All models produced estimates of age-1 + biomass and exploitation rate that were similar in trend and magnitude to the single-species statistical catch-at-age model, especially in recent years. While the less complex models were relativity easy to implement and update, they lacked key elements needed to manage multiple species simultaneously. More complex models required a wider array of data and were more difficult to update within the current management time-frames, but produced a more useful framework for managers. Ultimately, an EwE model of intermediate complexity coupled with the existing single-species assessment model was recommended for use in management.

Combining Ecosystem and Single-Species Modeling to Provide Ecosystem-Based Fisheries Management Advice Within Current Management Systems - Daniel Howell; Amy M. Schueller; Jacob W. Bentley; Andre Buchheister; David Chagaris; Matthew Cieri; Katie Drew; Mathieu G. Lundy; Debbi Pedreschi; David G. Reid; Howard Townsend (Frontiers in Marine Science, 2021)
Although many countries have formally committed to Ecosystem-Based Fisheries Management (EBFM), actual progress toward these goals has been slow. This paper presents two independent case studies that have combined strategic advice from ecosystem modeling with the tactical advice of single-species assessment models to provide practical ecosystem-based management advice. With this approach, stock status, reference points, and initial target F are computed from a single-species model, then an ecosystem model rescales the target F according to ecosystem indicators without crossing pre-calculated single-species precautionary limits. Finally, the single-species model computes the quota advice from the rescaled target F , termed here F eco . Such a methodology incorporates both the detailed population reconstructions of the single-species model and the broader ecosystem perspective from ecosystem-based modeling, and fits into existing management schemes. The advocated method has arisen from independent work on EBFM in two international fisheries management systems: (1) Atlantic menhaden in the United States and (2) the multi species fisheries of the Irish Sea, in the Celtic Seas ecoregion. In the Atlantic menhaden example, the objective was to develop ecological reference points (ERPs) that account for the effect of menhaden harvest on predator populations and the tradeoffs associated with forage fish management. In the Irish Sea, the objective was to account for ecosystem variability when setting quotas for the individual target species. These two exercises were aimed at different management needs, but both arrived at a process of adjusting the target F used within the current single-species management. Although the approach has limitations, it represents a practical step toward EBFM, which can be adapted to a range of ecosystem objectives and applied within current management systems.

Temporal variability in size and growth of Atlantic herring in the Gulf of Maine - James R. Becker; Matthew D. Cieri; David A. Libby; Adam St. Gelais; Graham Sherwood; Yong Chen (Journal of Fish Biology, 2020)
Variability in life history traits and structural diversity of commercially exploited fishes in response to stress can impact their population dynamics and sustainability. Using data from a fishery dependent sampling program from 1978 to 2011, we evaluated temporal variability of size and growth of adult Atlantic herring ( Clupea harengus ) in the Gulf of Maine. We then developed and tested the hypotheses on the links of such temporal changes to population density and environmental factors and found decreases in size and growth potential. Generalized additive models found that density dependence was the main driver of such changes over sea surface temperature and salinity. Our results highlight the importance of density dependent processes in regulating growth and population size structure for Atlantic herring in the Gulf of Maine.

Processing watershed‐derived nitrogen in a well‐flushed New England estuary - Craig R. Tobias; Matthew Cieri; Bruce J. Peterson; Linda A. Deegan; Joseph Vallino; Jeffrey Hughes (Limnology and Oceanography, 2003)
Isotopically labeled nitrate ( 15 NO 3 − ) was added continuously to the Rowley estuary, Massachusetts, for 22 d to assess the transport, uptake, and cycling of terrestrially derived nitrogen during a period of high river discharge and low phytoplankton activity. Isotopic enrichment of the 3.5‐km tidal prism (150,000 m 3 ) was achieved for the 3 weeks and allowed us to construct a nitrogen mass balance model for the upper estuary. Mean δ 15 NO 3 − in the estuary ranged from 300‰ to 600‰, and approximately 75%–80% of the 15 N was exported conservatively as 15 NO 3 − to the coastal ocean. Essentially all of the 20%–25% of the 15 N processed in the estuary occurred in the benthos and was evenly split between direct denitrification and autotrophic assimilation. The lack of water‐column 15 N uptake was attributed to low phytoplankton stocks and short water residence times (1.2–1.4 d). Uptake of watercolumn NO 3 − by benthic autotrophs (enriched in excess of 100‰) was a function of NO 3 − concentration and satisfied up to 15% and 25% of the total nitrogen demand for benthic microalgae and macroalgae, respectively. Approximately 10% of tracer assimilated by benthic autotrophs was mineralized and released back to the water column as 15 NH 4 + . By the end of the study, 15 N storage in sediments and marsh macrophytes accounted for 50%–70% of the 15 N assimilated in the estuary. These compartments may sequester watershed‐derived nitrogen in the estuary for time scales of months to years.